THE EFFECT OF ADDING TEMPE ON THE PHYSICAL QUALITY OF SKIPJACK FISH MEATBALLS (KATSUWONUS PELAMIS) - Kaliky, Nurainy; Wasahua, Tahir (Nindikayla Institute, 2024)
Meatballs are processed foods from fish meat that are liked by all people. Meatballs can be made from chicken, beef or fish. One of the fish that can be used for making fishballs is skipjack tuna (Katsuwonus pelamis). Skipjack tuna (Katsuwonus pelamis) is a pelagic fish and has economic value, usually exported abroad so that it can increase the country's foreign exchange. This fish has 2 colors of flesh, namely red and white. the white flesh of this fish will be processed into fish balls. Fish balls have a savory taste and chewy texture. Meatballs with a chewy texture and good quality are obtained by substituting certain ingredients to improve the quality of the meatballs. The material used is tempeh. Tempeh is a processed product from soybeans which contains vegetable protein. This study aims to determine the effect of adding tempe to cakalang fish balls, and to determine the extent of consumer acceptance of these fish balls. There were 2 treatments, namely A ( skipjack tuna) , B ( tempeh concentration ); B1 = 75 gr, B2 = 150 gr. With 2 repetitions. The results showed that taste, texture, folding had a significant effect and smell had no significant effect